2020
DOI: 10.1371/journal.pone.0231697
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the cold pressor test and pain sensitivity questionnaire via online self-administration

Abstract: ¶ Membership of the 23andMe Research Team is provided in the Acknowledgments.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…We could check this by assessing whether studies employed protocols from previously published work, or how homogenous protocols were across studies. Two studies were excluded due to a lack of methodological standardization [76,133] 4. Desirable statistics-Most studies provided Pearson's correlations for our variables of interest, but a few provided Spearman's rank correlations.…”
Section: Missing Data-mentioning
confidence: 99%
“…We could check this by assessing whether studies employed protocols from previously published work, or how homogenous protocols were across studies. Two studies were excluded due to a lack of methodological standardization [76,133] 4. Desirable statistics-Most studies provided Pearson's correlations for our variables of interest, but a few provided Spearman's rank correlations.…”
Section: Missing Data-mentioning
confidence: 99%
“…2 The PSQ total score has shown a modest correlation with experimental thermal pain threshold, tolerance, and intensity. 2,8,35 The PSQ contains 17 items: fourteen items relate to situations that are usually considered to be painful for most persons covering a variety of different pain qualities, while three items (items 5, 9, 13) describe normally non-painful situations. Pain magnitude is rated on a 0-10 scale with one anchor at 0, representing 'no pain at all', and the other anchor at 10, representing the 'worst pain one can imagine'.…”
Section: Self-reportedmentioning
confidence: 99%
“…Such approaches could be leveraged to quantify acute pain in the presence of RRI data from a range of sources, from ECG data in clinical settings to data derived from PPG in consumer wearables. The use of the CPT allowed for controlled, replicable pain induction promotes a moderately painful but rapidly reversible stimulus, as widely reported via self-report ( 31 ) or behavioral change ( 32 ). Given the high prevalence of pain worldwide, which reaches up to 25% of the population in some countries ( 33 ), and the lack of objective methods to classify pain, this approach has the potential to identify and better mitigate individual pain.…”
Section: Discussionmentioning
confidence: 99%
“…The average duration of the CPT was similar to previous studies ( 48 ), but the percentage of participants that did not complete the CPT was approximately double previously reported percentages ( 49 ). Duration of CPT has been used previously as a proxy for pain tolerance ( 32 ). In our study, participants found the CPT highly painful, unpleasant, difficult to complete, and stressful ( 49 ).…”
Section: Discussionmentioning
confidence: 99%